2016
DOI: 10.2147/cia.s120253
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between <em>FTO</em> rs9939609, <em>MC4R</em> rs17782313, and <em>PPAR&gamma;</em> rs1801282 polymorphisms and the occurrence of selected metabolic and hormonal disorders in middle-aged and elderly men &ndash; a preliminary study

Abstract: PurposeMetabolic disorders, including MetS, obesity, and lipid disorders, may be related to genetic factors. Metabolic disorders are associated with decreased TS levels in aging men. The aim of this study was to evaluate the relationship between FTO rs9939609, MC4R rs17782313, and PPARγ rs1801282 polymorphisms and the presence of MetS and its components, the concurrent lipid disorders, as well as sex hormone concentrations.Subjects and methodsThis study involved 272 men of Caucasian descent aged 50–75 years. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
4
3
0
1
Order By: Relevance
“…Lipid profile disturbances as a component of metabolic syndrome were also analysed in the conducted research. Similar to this study, other studies conducted in Poland [9,11] and Greece [14] did not find a statistically significant association between MC4R SNP in rs17782313 and the lipid profile of patients. There is only one study reporting a reduced risk of lipid disturbances among individuals with T allele in a group of Polish postmenopausal women [8].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lipid profile disturbances as a component of metabolic syndrome were also analysed in the conducted research. Similar to this study, other studies conducted in Poland [9,11] and Greece [14] did not find a statistically significant association between MC4R SNP in rs17782313 and the lipid profile of patients. There is only one study reporting a reduced risk of lipid disturbances among individuals with T allele in a group of Polish postmenopausal women [8].…”
Section: Discussionsupporting
confidence: 88%
“…In the presented work no significant association between MC4R SNP in rs17782313 and obesity was found. This observation is in line with two similar studies conducted in Poland [9,11] and one carried out in the Czech Republic [12]. On the contrary, other population studies conducted in Pakistan [13] and Greece [14] showed that homozygotes CC have a higher risk of obesity; similarly, in the Romania population heterozygotes CT are more predisposed to obesity [15].…”
Section: Discussionsupporting
confidence: 87%
“…Zhang, et al, 2014) and promotes metabolic syndrome (Keramati, et al, 2014). In addition to the list of genes mentioned above, genetic polymorphism of the lamin A/C (LMNA) (Ji, et al, 2016), insulin receptor substrate 1 (IRS1) (Kloting & Bluher, 2014), melanocortin receptor 4 (MC4R) (Ruiz-Ramirez, Lopez-Acosta, Barrios-Maya, & El-Hafidi, 2016), TCF7L2 (transcription factor 7-like 2) (Palizban, Rezaei, Khanahmad, & Fazilati, 2017), fat mass and obesity associated gene (FTO) (Elouej, et al, 2016; Rotter, et al, 2016) have also been documented to be associated with increased prevalence of cardiorenal metabolic syndrome.…”
Section: Pathophysiology Of the Cardiorenal Metabolic Syndromementioning
confidence: 99%
“…This is supported by the associations we observed between FTO variants and components of the MetS, particularly with WC and SBP. Various candidate gene studies have observed association between FTO variants and MetS in adults 71,73,77,93 across different ethnicities 73,76,93,94 . Our results confirm the association of FTO variants and MetS in children and adolescent populations via its implication in the regulation of body fatness.…”
Section: Discussionmentioning
confidence: 99%